Growth hormone administration and exercise combination increase serum IGF-1 levels in perimenopausal wistar rats - Ni Luh Kadek Alit Arsani; Luh Putu Ratna Sundari (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Growth hormone (GH), Insulin-like growth factor 1 (IGF-1), and exercise play a crucial role in female reproductive function. At the perimenopausal age, there is a decrease in GH, estrogen, and testosterone levels. In previous studies, the impact of physical activity on serum IGF-1 levels in geriatric was inconsistent and needed further investigation. Objective: The purpose of this study was to look into the effect of GH and exercise on serum IGF-1 levels in perimenopausal Wistar rats. Methods: It is an experimental study with a randomized posttest-only control group design using 24 perimenopausal Wistar rats aged 14 months as the sample. The control rats (C) were given 0.1 ml of distilled water subcutaneously every day for 30 days. Treatment group 1 (T1) rats swam for 30 minutes at a time five times per week. Meanwhile, rats of T2 were given 0.016 IU/0.1ml GH daily injection subcutaneously only for 30 days and T3 were given combination both of GH injection in same dose and swam for 30 minutes at a time 5 times a week for 30 days Data analysis used One-Way ANOVA.Results: The finding revealed that the mean serum IGF-1 levels in the T3 (588.50 84.04 ng/mL) were significantly higher than the control (242.03 ± 46.08 ng/mL), T1 (334.23 ± 75.90 ng/mL) and T2 (428.69 ± 95.10 ng/mL). Conclusion: Our study shows that GH administration and exercise combination increases levels of IGF-1 serum higher than only administrated GH or exercise.